BM and FBOVESPA Sustainability Index and the Responsible Practices of Brazilian Corporations : Issue Brief - International Finance Corporation (Washington, DC, 2017)
BM and FBOVESPA, Latin America’s leading exchange in number of transactions and one of the world’s largest in market value, created the corporate sustainability index (ISE índice de sustentabilidade empresarial) in 2005 with financial support from the International Finance Corporation (IFC). The ISE was designed to create an efficient investment mechanism to group companies with superior performance that manage environmental, social, and governance risks and opportunities. The ISE served as a reference guide for initiation of sustainability practices as well as for their continuous improvement. The firms that have been in the index (for some time or since its inception) report valuable benefits in terms of improved sustainability practices, better reputation, and, to some extent, positive impacts on their stock price, access to capital, and liquidity in the stock market. The ISE supported a rapid move to sustainable practices among listed firms, with most relatively large companies with liquid stocks eager to participate. As experience has been gained, the requirements for membership have been tightened, and fewer firms have been applying. IFC’s strategy in Brazil focuses on promoting access to finance and developing capital markets to reach low-income individuals, microenterprises, and small businesses. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.